(untitled) (Global Journal of Medical Research, 2023)
Infection of SARS-COV2 and its variants causes wide range morbidity and mortality in recent years Identification of epitope-based mechanism of viral infection with progressive fatality and antiviral immunotherapy are two major goals to address population-bias immune response We selected peptides from SARS-COV2 Spike 6VXX_A Delta B 1 617 2 Omicron B 1 1 529 proteins These peptides contain epitopes which are identified as low rank good fit immunogenic as recognized more by HLA-DRB1 15 01 than HLA-DRB1 07 01 and HLA-DRB1 03 01 We also found the selected epitopes specifically form interactive complex with mucosa-associated invariant T cell The Molecular Docking and Molecular Dynamics experiments demonstrated amino acid sequence-specific interaction between close atoms from epitopes and MAIT-TCR We used virus unrelated microbial peptide antigen85 as control